557 Becoming Virtual: Lessons Learned from Moving Wessex Core Surgical Training Deanery Teaching On-Line. (12th October 2021) - Robinson, P; Morton, L; West, C
Abstract: Aim: Surgical training has been significantly impacted by COVID-19. Social distancing requirements mandated a change in face-to-face teaching with many deaneries adopting 'virtual' sessions. Surgical training does not immediately lend itself to e-learning owing to its hands-on nature. We describe our experiences in developing a virtual teaching program for Core Surgical Trainees within the Wessex Deanery. We provide tips, tricks, and pitfalls for educators to establish or improve similar programs. Method: From June 2020 monthly, in-person teaching was replaced with virtual sessions. Quantitative and qualitative feedback directed improvements in the program. In addition to knowledge-based lectures we integrated on-line learning tools (LapPass) and utilised surgical videos to ensure continued development of surgical skills. Mock MRCS and ST3 interviews were conducted remotely using 'break-out rooms. Where face-to-face teaching was essential (Boot Camp, Field Camp) safety was ensured with reduced numbers (split sessions), social distancing and appropriate PPE. Results: All trainees strongly agreed (67%) or agreed (33%) that virtual teaching works well. There were no significant differences in feedback scores compared with face-to-face teaching. Attendance increased by 42%. Interactivity was maintained with 'cameras on, mics off', polling apps and chat box function. Advantages include uploading webinars for future review, ability for educators to present from multiple locations, increased availability and breadth of speakers and reduced burden on clinical commitments. Conclusions: The COVID-19 pandemic has dictated an evolution of surgical teaching. Virtual teaching has many advantages over face-to-face and should continue to play a part in postgraduate medical education, even after social distancing restrictions are lifted.